Reflexões sobre o Racismo Estrutural no Documentário ' A Carne mais Barata no Mercado é a Carne Negra - JEFERSON SOUZA DOS SANTOS (2023)
The objective of this work is to analyze the structural racism that exists in our society, through the analysis of the documentary “The Cheapest Meat on the Market is Black Meat”